Turn left at the end of the world - Atika, Aure 1970-; Benguigui, Jean 1944-; Garty, Neta 1980-; Ts'arkhi, Liraz (United King Films, 2007)
"The movie tells the story of the immigration to Israel of Jews from two distinct backgrounds in the 1960's, and their settlement in the Negev towns of Dimona and Yeruham. Indian Jews arrived looking for a better life in the West, only to find themselves in the desert. With their English Colonial hangover, and the French background of the Moroccan immigrants, there is an inevitable clash of cultures, made worse when a married Indian man falls in love with a young Moroccan girl. The story comes to a climax when it is heard that the English cricket team will be stopping in the Negev for a match, and the two groups have to work together to produce a team capable of taking on the powerful English"--Israel Cricket Association web site
DVD (PAL, region 2), widescreen, Dolby digital 5.1. - Original idea by Avi Nesher. - Originally produced as a motion picture in 2003. - A foreign film (Israel and France). - Special features include the making-of, slides of casting, deleted scenes, 2 video clips, commentary by director, interviews, trailer
Keywords: Feature films; DVD-Video